Sensor node acceleration signatures and electromyography in synchronisation and sequencing analysis in sports: A rowing perspective - Armstrong, S.; Nokes, L. D. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
Following a review of the key determinants of successful rowing, a wireless body sensor network was developed to monitor boat and body segment acceleration and surface electromyography in major muscles recruited during the rowing stroke cycle. Its design was optimised to yield maximum information about the rowing stroke cycle from fewest sensors and minimise the power consumption of the nodes. The system was validated against the Qualisys motion capture and high-speed camera system with most Pearson correlation coefficients in excess of r = 0.8. On-land ergometer experimentation allowed muscle recruitment over the stroke cycle to be studied, with data from multiple experiments combined using correlation of the acceleration signatures of back and thigh nodes (r = 0.95). It was demonstrated that it was possible to identify one of the common rowing errors of `shooting-the-slide` from the data collected, and that a marked decrease in correlation of good-to-bad technique over the drive phase of the stroke (0.95 reducing to 0.34 in the experiment undertaken) could be used to indicate the presence of this error. Extension of the wireless body sensor network to encompass boat and two oarsmen was demonstrated, allowing correlation of their rowing signatures to be studied, indicating their cohesion as a crew.